1993
DOI: 10.1002/mcs.1220050505
|View full text |Cite
|
Sign up to set email alerts
|

tert‐Butyldimethylsilyl‐substituted cyclodextrin derivatives as versatile chiral stationary phases in capillary GC

Abstract: Abstract, tert-Butyldimethylsilylated cyclodextrin derivatives dissolved in polysiloxanes were shown to be versatile chiral stationary phases for the differentiation of important chiral food and flavor ingredients and chiral acids of biochemical and pharmaceutical interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…silyl group TBDMS unexpectedly have a broad w x enantioselectivity. Mosandl et al 6 confirmed enantioselectivity of TBDMS-␤-and ␥-CDs by sepa-rating the enantiomers of several other structurally w x different racemates. Kobor and Schomburg 7 showed that TBDMS-CD enantioselectivity could be related to the different shapes of these derivatives w x compared to 6-AL-CDs.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…silyl group TBDMS unexpectedly have a broad w x enantioselectivity. Mosandl et al 6 confirmed enantioselectivity of TBDMS-␤-and ␥-CDs by sepa-rating the enantiomers of several other structurally w x different racemates. Kobor and Schomburg 7 showed that TBDMS-CD enantioselectivity could be related to the different shapes of these derivatives w x compared to 6-AL-CDs.…”
Section: Introductionmentioning
confidence: 75%
“…This is more difficult than the separation of high-to-medium volatility racemates, because GC enantioseparation with CDs is thermodynamically driven and therefore influenced by the w x analysis temperature. Mosandl et al 6 suggested Ž using shorter and thinner film columns 0.05 m . and 15 m to keep the elution temperature below 200ЊC for the separation of the enantiomers of 2-hydroxy-acid methyl esters and higher ␦-lactone homow x logues, while Koenig et al 13 adopted higher flow rates to separate pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…For example, DIME-6-TBDMS-0-CD shows only a weak selectivity for 2-ethylhexanoic acid which is included in one of the tests. However, this chiral stationary phase was successfully applied for stereodifferentiation of various other alkyl branched free fatty acids [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…CDs are generally used diluted in apolar or moderately polar polysiloxanes to obtain high efficiency capillary GC columns, in agreement with the approach proposed by Schurig et al [1,2] b-and c-CDs substituted in positions 2 and 3 with methyl (ME) or acetyl (AC) groups and in position 6 with t-butyldimethylsilyl (TBDMS) or t-hexyldimethylsilyl (THDMS) are among the most effective derivatives used as chiral selector for enantioselective GC [3,4] and show enantioselectivities that are very often complementary.…”
Section: Introductionmentioning
confidence: 93%